Dialectics of Types of Legal Regulation Testing from the Perspective of Authority and Effectiveness through the Study of Constitutional Court Decision Number 30/PUU-XVI/2018 and Supreme Court Decision Number 65 P/HUM/2018 - Naufal Nuryasir Hibaatullah; Nurul ‘Izzul Umami; Reyhana Luthfiyah Sari; Vironika Dewi; Utang Rosidin (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
This article examines the dialectics of judicial review of laws and regulations in Indonesia from the perspective of authority and effectiveness, with a particular focus on the Constitutional Court Decision Number 30/PUU-XVI/2018 and the Supreme Court Decision Number 65 P/HUM/2018. The research aims to analyze the classification and characteristics of judicial review, the mechanisms and institutional authority involved, and the legal implications arising from differences in review models exercised by the Constitutional Court and the Supreme Court. This study employs normative legal research using a statutory approach and a case approach. Primary legal materials include the 1945 Constitution of the Republic of Indonesia, statutes governing judicial authority, and relevant court decisions, supported by secondary legal materials from scholarly literature. The analysis is conducted qualitatively through deductive legal reasoning. The findings indicate that the dualism of judicial review authority, while normatively intended to maintain hierarchical order of norms, in practice generates potential disharmony in legal interpretation and weakens legal certainty. Differences in review orientation—constitutional-based review by the Constitutional Court and legal-formal review by the Supreme Court—may result in fragmented implementation of constitutional norms. Therefore, strengthening constitutional supremacy and harmonizing judicial interpretation between both institutions are essential to ensure consistency, effectiveness, and protection of constitutional rights within Indonesia’s legal system.